Adsorption Performance of Tetracycline on Yellow River Sediment - Zhu1, Lingfeng; Fan2, Jinzhou; Ye1, Zhao; Wang1, Binbin; Li1, Guoting (Asian Journal of Chemistry, 2014)
Pharmaceuticals and personal care products have aroused increasing concern throughout the world due to their wide occurrence in natural waters and direct threat to human beings. In this study, tetracycline , one of the pharmaceuticals and personal care products was selected as a target pollutant to check its adsorption behavior on Yellow river sediment. This will help understanding about its transportation in Yellow river and potential risk for human beings. Adsorption kinetics and isotherm tests were conducted for the sediments collected from Huayuankou (Zhengzhou city, China), the middle reach of Yellow river. Effect of solution pH and natural organic matters were also investigated. It was observed that solution pH had a dramatic influence on tetracycline adsorption while the maximal uptake of tetracycline achieved 40.8 mg/g at equilibrium pH 5. Elovich kinetic model could describe the adsorption kinetics better than pseudo-first-order and pseudo-second-order models. The isotherm data were well fitted by Langmuir, Freundlich, Toth and Redlich-Peterson models. The coexisting natural organic matter (humic acid) significantly inhibited the uptake of tetracycline onto Yellow river sediment.